MicroRNA-126 Modulates Palmitate-Induced Migration in HUVECs by Downregulating Myosin Light Chain Kinase via the ERK/MAPK Pathway - Wang, Yi; Wang, Mei; Yu, Pei; Zuo, Li; Zhou, Qing; Zhou, Xiaomei; Zhu, Huaqing (Frontiers in Bioengineering and Biotechnology, 2020)
MicroRNA-126 (miR-126) is an endothelial-specific microRNA that has shown beneficial effects on endothelial dysfunction. However, the underlying molecular mechanism is unclear. Palmitate, a major endogenous free fatty acids induce endothelial dysfunction which contributes to the pathogenesis of cardiovascular disease. The present study evaluated the effects of miR-126 on the cell migration and underlying mechanism in HUVECs treated with palmitate. The present results demonstrated that treated with palmitate, miR-126 expression was downregulated, cell migration was increased and MLCK expression was upregulated. Furthermore, overexpression of miR-126 was found to decrease cell migration in palmitate-treated HUVECs, with decreased MLCK expression and subsequent decreased phosphorylated MLC levels. miR-126 also decreased the phosphorylation of MYPT1 in palmitate-treated HUVECs. In addition, it was demonstrated that miR-126 decreases expression of the NADPH oxidase subunits, p67 and Rac family small GTPase 1 with a subsequent decrease in cell apoptosis. Moreover, the phosphorylation of ERK was reduced by miR-126 in palmitate-induced HUVECs. Taken together, the present study showed that the effect of miR-126 on cell migration and cell apoptosis is mediated through downregulation of MLCK via the ERK /MAPK pathway.